2021
DOI: 10.1093/mnras/stab1587
|View full text |Cite
|
Sign up to set email alerts
|

Fast magnetoacoustic wave trains: from tadpoles to boomerangs

Abstract: Rapidly propagating fast magnetoacoustic wave trains guided by field-aligned plasma non-uniformities are confidently observed in the Sun’s corona. Observations at large heights suggest that fast wave trains can travel long distances from the excitation locations. We study characteristic time signatures of fully developed, dispersive fast magnetoacoustic wave trains in field-aligned zero-β plasma slabs in the linear regime. Fast wave trains are excited by a spatially localised impulsive driver and propagate alo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…A number of studies theoretically supported that the waveguide-caused dispersion leads to the formation of quasi-periodic wave trains (e.g. Nakariakov et al, 2004;Li et al, 2018;Kolotkov et al, 2021). This view has been confirmed by observations (e.g.…”
Section: Introductionmentioning
confidence: 68%
“…A number of studies theoretically supported that the waveguide-caused dispersion leads to the formation of quasi-periodic wave trains (e.g. Nakariakov et al, 2004;Li et al, 2018;Kolotkov et al, 2021). This view has been confirmed by observations (e.g.…”
Section: Introductionmentioning
confidence: 68%
“…The typical feature of tadpole wavelet spectrum has been used as a characteristic signature for identifying the presence of possible QFP wave trains in both observational and numerical studies, when direct imaging of QFP wave trains in EUV were unavailable (e.g., Mészárosová et al, 2009bMészárosová et al, , 2013Karlický, Jelínek, and Mészárosová, 2011;Karlický, Mészárosová, and Jelínek, 2013;Jelínek, Karlický, and Murawski, 2012;Mészárosová et al, 2014). Recently, Kolotkov et al (2021) modeled the linear dispersively evolving of QFP wave trains in plasma slabs with varying steepness of the transverse density profile, in which they showed that the development of a QFP wave train evolved from an initial impulsive perturbation undergoes three distinct phases fully consistent with that qualitatively predicted by Benz (1983, 1984). In contrast to wave trains in smooth waveguides that produce the tadpole structures (Nakariakov et al, 2004), it is interesting that the wavelet power spectrum develops into a boomerang structure that has two pronounced arms in the longer-and shorter-period parts of the spectrum (see the right column of Figure 12).…”
Section: Dispersion Evolution Mechanismmentioning
confidence: 99%
“…The right column shows the time profile (top) and wavelet power spectrum (bottom) of a fully developed fast sausage wave train in a steep plasma waveguide. The three distinct developing phases of the wave train are indicated in the figure, and the wavelet spectrum shows a boomerang shape (Kolotkov et al, 2021).…”
Section: Dispersion Evolution Mechanismmentioning
confidence: 99%
“…These fast wave trains are observed in various wavelength bands in the corona (Williams et al 2001;Li et al 2020, and references therein). They are examined analytically by Roberts et al (1984) and Oliver et al (2015), and numerically by e.g., Nakariakov et al (2004); Yu et al (2017); Kolotkov et al (2021). As demonstrated in e.g., Roberts et al (1984), the temporal signature of axisymmetric wave trains consists of distinct phases when observed sufficiently far from the exciter.…”
Section: Introductionmentioning
confidence: 99%